Species identification and molecular characterization of Cronobacter spp. isolated from food imported over nine years into Beijing, China. (September 2019) - Wang, Qi; Forsythe, Stephen James; Zhao, Xiao-Juan; Wang, Zi-Wei; Li, Dan; Ma, Dan; Cao, Jia-Yue; Zeng, Jing
Abstract: Cronobacter spp. are associated with serious infections in neonates with the clinical presentations of necrotizing enterocolitis, bacteraemia and meningitis. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was used to identify 203 Cronobacter isolates from imported food during 2006–2015 with an optimized in-house database. The isolates were predominantly C. sakazakii (88.18%), followed by C. malonaticus (8.37%), C. muytjensii (1.48%), C. turicensis (0.99%) and C. dublinensis (0.99%). The result was totally consistent with that of fusA allele sequencing. 12.32% (25/203) of isolates gave inconsistent spectra following separate protein extractions. Sixty C. sakazakii isolates and 24 isolates from the other four s pecies were chosen for multi-locus sequence type analyses (MLST) and PCR-serotyping. Thirty-one sequence types were identified. The common sequence types were ST1 (19/60) and ST4 (13/60) for C. sakazakii and ST7 (12/17) for C. malonaticus. The primary serotypes were Csak O:1 (30/60), Csak O:2 (25/60) and Cmal O:2 (16/17) for C. sakazakii and C. malonaticus isolates, respectively. In conclusion, appropriate in-house database could make MALDI-TOF MS method identifying Cronobacter spp. isolates to the species level. But the spectra data were not sufficiently consistent for subtyping, unlike MLST. The Cronobacter spp. isolates have a high diversity including recognized pathovars. Highlights: MALDI-TOF MS can identify Cronobacter isolates to the species level. MALDI-TOF spectra of Cronobacter species are not sufficiently consistent for subtyping. 7-loci MLST is a more reliable method for subtyping Cronobacter species. Nine STs (ST614-ST619, ST624, ST625 and ST478) were newly assigned. The isolates were highly divergent and included recognized pathovars.